Homogeneously Oriented Organic Single‐Crystalline Patterns Grown by Microspacing In‐Air Sublimation. Issue 4 (19th February 2023) - Lin, Qinglian; Ye, Xin; Guo, Qing; Zheng, Xiaoxin; Han, Quanxiang; Li, Cuicui; Jiang, Jinke; Liu, Yang; Tao, Xutang
Abstract: Fabrication of single‐crystalline organic semiconductor patterns is of key importance to enable practical applications. However due to the poor controllability on nucleation locations and the intrinsic anisotropic nature of single‐crystals, growth of single‐crystal patterns with homogeneous orientation is a big challenge especially by the vapor method. Herein a vapor growth protocol to achieve patterned organic semiconductor single‐crystals with high crystallinity and uniform crystallographic orientation is presented. The protocol relies on the recently invented microspacing in‐air sublimation assisted with surface wettability treatment to precisely pin the organic molecules at desired locations, and inter‐connecting pattern motifs to induce homogeneous crystallographic orientation. Single‐crystalline patterns with different shapes and sizes, and uniform orientation are demonstrated exemplarily by using 2, 7‐dioctyl[1]benzothieno[3, 2‐b][1]benzothiophene (C8‐BTBT). Field‐effect transistor arrays fabricate on the patterned C8‐BTBT single‐crystal patterns show uniform electrical performance: a 100% yield with an average mobility of 6.28 cm 2 V −1 s −1 and in a 5 × 8 array. The developed protocols overcome the uncontrollability of the isolated crystal patterns in vapor growth on non‐epitaxial substrates, making it possible to align the anisotropic electronic nature of single‐crystal patterns in large‐scale devices integration. Abstract : Vapor‐growth of organic single‐crystal patterns for large‐scale field‐effect transistors integration is realized based on microspacing in‐air sublimation. To overcome inconsistent in‐plane orientation of the discrete anisotropic single‐crystals, surface wettability patterns with inter‐connecting motifs are designed to induce a homogeneous orientation among the whole patterned single‐crystalline film.